THE ADAPTATION OF CYBER SALAFISM DAʿWAH IN HADĪTH AḤKĀM LITERATURE: ANALYZING ʿUMDAT AL-AḤKĀM SERMONS ON THE YUFID CHANNEL - Ardiansyah, Ardiansyah; Firmansyah, Heri; Aniq, Ahmad Fathan (Universitas Islam Negeri Ar-Raniry, 2025)
This article examines how Salafism adjusts conservative literature with its preaching on YouTube. Over the last decade, Salafism has gained significant traction in Indonesian cyberspace and urban centers. Moreover, the impact of expanding preaching through social media platforms, such as Instagram, YouTube, and Facebook, has proven successful in increasing their popularity in urban areas. Therefore, uncovering the modification of conservative law literature in cyber-Salafism is significant because it not only captures the method of Salafism in online preaching but also reveals how Islamic classical books are adapted for online media. The object of this study is 240 Yufid videos discussing ʿUmdat al-Aḥkām. Therefore, this study employs an online ethnographic method in order to collect, classify, and analyze the data. Moreover, it is also applied to defining the setting of the research, feeding insight to the studied community, and presenting the results with ethical awareness. This study revealed that Yufid’s interpretation of ʿUmdat al-Aḥkām tends to be textual and seems indifferent to the social conditions of the surrounding community. Moreover, it also uncovered how ʿUmdat al-Aḥkām sermons manifest the business purpose of Yufid rather than theological demand. Through this research, we suggest that the government or scholars can monitor online preaching on YouTube channels as an extension of real movements.